Intrinsic Value of Stocks of “Big Oil” Companies - CHRASCINA, Marek; VANĚK, Michal; PEKARČÍKOVÁ, Kateřina (GeoScience Engineering, 2024)
This research investigates the intrinsic value of stocks of companies within the oil extraction sector. The focus is on publicly traded corporations part of “Big Oil”: ExxonMobil Corporation, Chevron Corporation, TotalEnergies SE, BP plc, Shell plc, and ENI S.p.A. The numerous fundamental analysis intrinsic value of stocks models is being applied to the Big Oil consortium. This article stands out for its unique focus on utilizing dividend discount models, earnings models, and cash flow models to calculate the intrinsic value of stocks in major oil companies, which is currently missing in existing studies as of April 2024. Through this approach, it not only forecasts stock prices but also provides investment recommendations, offering fresh insights into stock evaluation and uncovering potential investment prospects within these companies according to intrinsic value of stocks. Specific mathematical models for the intrinsic value of stocks are applied to each examined company for this calculation. The intrinsic value of stocks in companies recommended for investment was found to be undervalued by 7.25% for dividend discount models, 8.25% for earnings models, and 36.75% for cash flow models compared to their current market values. The assessment of intrinsic value of stocks reveals the suitability of investing in these companies: TotalEnergies SE, BP plc, Shell plc, ENI S.p.A. These results offer valuable insights for stock investors in the oil sector, as well as organizations under investigation and other stakeholders in the oil extraction industry.